2011
DOI: 10.1021/ic102309r
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Sulfide and Cadmium Phosphide Thin Films from a Single Cadmium Compound

Abstract: Aerosol-assisted chemical vapor deposition of Cd[(SP(i)Pr(2))(2)N](2) leads to the growth of cadmium sulfide and/or phosphide thin films on glass. Decomposition of the precursor has been studied by pyrolysis-gas chromatography/mass spectrometry and modeled by density functional theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…43,44 AACVD of [Cd{(SP i Pr 2 ) 2 N} 2 ] resulted in the formation of hexagonal CdS at deposition temperatures of 500 1C but growth of cubic Cd 6 P 7 and orthorhombic Cd 7 P 10 at 525 1C. 43,44 AACVD of [Cd{(SP i Pr 2 ) 2 N} 2 ] resulted in the formation of hexagonal CdS at deposition temperatures of 500 1C but growth of cubic Cd 6 P 7 and orthorhombic Cd 7 P 10 at 525 1C.…”
Section: Groups 12 and 16 (Ii-vi) Thin Filmsmentioning
confidence: 99%
“…43,44 AACVD of [Cd{(SP i Pr 2 ) 2 N} 2 ] resulted in the formation of hexagonal CdS at deposition temperatures of 500 1C but growth of cubic Cd 6 P 7 and orthorhombic Cd 7 P 10 at 525 1C. 43,44 AACVD of [Cd{(SP i Pr 2 ) 2 N} 2 ] resulted in the formation of hexagonal CdS at deposition temperatures of 500 1C but growth of cubic Cd 6 P 7 and orthorhombic Cd 7 P 10 at 525 1C.…”
Section: Groups 12 and 16 (Ii-vi) Thin Filmsmentioning
confidence: 99%
“…18,26 Aerosol-assisted chemical vapour deposition (AACVD) has been used to deposit a wide range of metal chalcogenide thin films. [27][28][29] Several adducts of cadmium dithiocarbamate complexes have recently been reported but without exploring their capabilities as precursors for AACVD. [15][16][17] Ehsan et al used bis(N,N-dicyclohexyldithiocarbamato)pyridinecadmium(II) to deposit greenockite CdS thin films which proved to be suitable for application in photoelectrochemical (PEC) cells.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Using this methodology, various functional inorganic materials for example,graphene, carbon nanotubes,s upported catalytic and semiconducting materials have been synthesized. [12] Recently,i th as also been observed that far more molecular precatalysts than assumed previously undergo complete degradation to form catalytically active solid materials under ambient operating conditions.T ypically,t he use of,f or example,e lectric potential, photo irradiation, strong chemical oxidants,have been shown to produce active inorganic materials that serve as real performing catalysts. [13] Over the last decade,w ew ere actively involved in the synthesis of new functional materials with unique inherent chemical and physical properties.T he majority of the work that we have conducted is based on the design of metalalkoxide and metal-silamide-alkoxidem olecular precursors for the synthesis of metal oxide and silicate materials that find applications in the field of modern electronics and sensors ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%